2023
DOI: 10.12688/f1000research.139258.1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Maslach Burnout Inventory in healthcare professionals, Ancash Region, Peru

Rosario Margarita Yslado Méndez,
Junior Sánchez-Broncano,
Carlos De La Cruz-Valdiviano
et al.

Abstract: Background: Burnout syndrome (BS) among healthcare professionals in Peru demands immediate attention. Consequently, there is a need for a validated and standardized instrument to measure and address it effectively. This study aimed to determine the psychometric properties of the Maslach Burnout Inventory (MBI) among healthcare professionals in the Ancash region of Peru. Methods: Using an instrumental design, this study included 303 subjects of both sexes (77.56% women), ranging in age from 22 to 68 years (M = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…58 Therefore, 63 cases were removed to obtain a final database consisting of 303 participants, which allowed for a better estimation in the conducted statistical analyses. 88 It's crucial to mention that the sample size achieved in this study surpasses the suggested minimum of 300 cases for studies utilizing factor analysis. 76 ).…”
Section: Resultsmentioning
confidence: 81%
“…58 Therefore, 63 cases were removed to obtain a final database consisting of 303 participants, which allowed for a better estimation in the conducted statistical analyses. 88 It's crucial to mention that the sample size achieved in this study surpasses the suggested minimum of 300 cases for studies utilizing factor analysis. 76 ).…”
Section: Resultsmentioning
confidence: 81%
“…For example, the Copenhagen Burnout Inventory, which assesses personal, work-related, and client-related burnout [ 72 ]; the Oldenburg Burnout Inventory, which assesses exhaustion and detachment from work [ 73 ]; and other instruments that are less commonly used in the development of research on BS. However, a review found that the MBI is currently the most widely used instrument [ 74 ], and several studies have demonstrated its psychometric properties [ 40 , 75 , 76 ], so we believe that using only the MBI is justified. Finally, the studies found used different versions of the MBI and different cut-offs to determine levels and dimensions of burnout.…”
Section: Discussionmentioning
confidence: 99%